Perceived social support and psychological wellbeing: testing the moderated mediation model of self-compassion and culture - Tannous-Haddad, Lubna; Barel, Efrat; Tzischinsky, Orna (Frontiers in Psychology, 2024)
Introduction Self-compassion and self-coldness mediate the relationship between perceived social support and wellbeing, depression, anxiety and stress. However, this mediation has not been studied in intercultural contexts yet. The current crosssectional study explores the mediation effects of both constructs among Arabs and Jews in Israel. Methods Participants were 496 adults—309 Jews (62.3%) and 187 Arabs (37.7%) with an average age of 40.3. Respondents completed online standardized measures of self-compassion, self-coldness, perceived social support, wellbeing, depression, anxiety, and stress. The data were analyzed using PROCESS macro model 4 and 59. Results Testing the indirect effects of self-compassion and self-coldness on the relationship between perceived social support and wellbeing facets, we found a mediation effect for both constructs. We also found that culture moderated the mediation processes and found a stronger mediation effect for self-compassion among Arabs than Jews, but no moderation of culture on the mediation effect of self-coldness. Discussion These results emphasize the importance of considering cultural context when designing support interventions aimed at promoting wellbeing by enhancing self-compassion. The differential mediation effect by self-compassion and self-coldness contributes to growing research pointing to a need to further explore the influence of different components of self-compassion in different cultures.